2011
DOI: 10.1002/lary.22392
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical validation of AR42, a novel histone deacetylase inhibitor, as treatment for vestibular schwannomas

Abstract: Objective/Hypothesis Recent studies indicate that vestibular schwannomas (VS) rely on PI3-kinase/AKT activation to promote cell proliferation and survival; therefore, targeting AKT may provide new therapeutic options. We have previously shown that AR42, a novel histone deacetylase inhibitor, potently suppresses VS growth in vitro at doses correlating with AKT inactivation. The objectives of the current study were translational: 1) to examine the end biologic effects of AR42 on tumor growth in vivo, 2) to valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 100 publications
0
46
1
Order By: Relevance
“…6 Additionally, while we did not examine Akt signaling in the current study, others have demonstrated that Akt signal inhibition (by AR42 and other agents) sensitized CP70 and other p53-dysfunctional, drug-resistant, ovarian cancer cells. 37,56 As AR42 has also been demonstrated to downregulate Akt activity, [7][8][9]12 blockade of that oncogenic signal pathway might represent another HDACI mechanism of resensitization of chemoresistant ovarian cancer cells (an antineoplastic effect we previously observed). 6 Similar to EMT, gene set enrichment analysis 35 also demonstrated AR42 gene expression profiles to negatively associate transition (EMT) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Additionally, while we did not examine Akt signaling in the current study, others have demonstrated that Akt signal inhibition (by AR42 and other agents) sensitized CP70 and other p53-dysfunctional, drug-resistant, ovarian cancer cells. 37,56 As AR42 has also been demonstrated to downregulate Akt activity, [7][8][9]12 blockade of that oncogenic signal pathway might represent another HDACI mechanism of resensitization of chemoresistant ovarian cancer cells (an antineoplastic effect we previously observed). 6 Similar to EMT, gene set enrichment analysis 35 also demonstrated AR42 gene expression profiles to negatively associate transition (EMT) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies by our group and others have similarly shown potential therapeutic efficacy of a "rationally designed" HDACI, AR42 (formerly OSU-HDAC42, Arno Therapeutics), 5 against multiple myeloma, adult T-cell lymphomas and solid tumors of the ovary, liver and prostate, both singly or combined with other agents. [6][7][8][9][10][11][12] Various molecular mechanisms/processes have now been advanced to explain HDACI cancer cell-specific cytotoxicity (and non-toxicity toward normal cells), including upregulation of pro-apoptotic genes, downregulation of anti-apoptotic genes, abrogation of cell cycle checkpoints and increased production of reactive oxygen species (concurrent with diminished antioxidative response). 2,4 With some exceptions, however, many of those previously identified anticancer mechanisms were based on limited numbers of HDACI-altered genes, absent rigorous assessments of HDACI cumulative effects on signal pathways/ networks.…”
Section: Hdac Inhibitor Effects On Microrna and Mrna Expressionmentioning
confidence: 99%
“…The combination prior to the start of any experiment. Three days after whole body irradiation (400 rads), 5 × 10 6 Raji cells in 100 μL PBS were implanted subcutaneously in the flank to establish tumors. After tumors reached >300 mm 3 , mice were randomly assigned to one of four treatment groups (7 animals/group): control (vehicle only), CHEK2i (1.0 mg/kg/dose), AR42 (10 mg/kg/dose), or combination of CHEK2i (1.0 mg/kg/dose) and AR42 (1.0 mg/kg/dose).…”
Section: Cytotoxic Effects Of Ar42 and Chek2i On Nhl Cell Linesmentioning
confidence: 99%
“…Currently, three such drugs are FDA-approved for the treatment of NHL (vorinostat, belinostat and romidepsin); a number of others are in clinical development for various hematologic malignancies (17,18). AR42, a phenylbutyrate-derived pan-HDACI, has been shown to have cytotoxic activity in several malignancies (4)(5)(6)(7)9,19,20). More recently, AR42 and other HDACIs have been reported to synergistically increase the cytotoxic activity of the α-CD22 monoclonal antibody (mAb) HB22.7 (14) and the α-CD20 mAb rituximab (11-13) on NHL cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation